Sound Absorption Of Micro-Perforated Panel Made By Oil Palm Fibre - Lim, Mei Hui (Universiti Sains Malaysia, 2021)
This study presents the sound absorption performance of micro-perforated panel (MPP) made by oil palm fibre. Firstly, samples are fabricated from oil palm fibre and perforated by using Computer Numerical Control (CNC) machine with a hole diameter of 1 mm. After that, an impedance tube experiment is carried out and the measured results show that the sound-absorbing panel with MPP structure generates a better acoustic performance, comparing to the sound-absorbing panel without MPP structure. MPP with a perforation ratio of 0.8 % shows the greatest peak sound absorption coefficient (SAC) of 0.77 at the frequency of 600 Hz, comparing to the panel without MPP structure, which produces a peak SAC of 0.20 at the same frequency range. The predicted and measured results obtained from the modelling equation of MPP and impedance tube experiment respectively are then compared. Some deviations occur between the results due to the trapped air bubbles inside the samples during fabrication process. Moreover, it is observed that the panel vibration effect significantly modifies the sound absorption performance of thin MPP, which has a panel thickness of 1 mm. Meanwhile, it does not alter the SAC of rigid MPP, which has a panel thickness of 3 mm. Apart from that, it is observed that as the air cavity depth increases, the maximum SAC of the MPP shifts to a lower frequency range. Besides, it is noticed that the peak SAC is decreased and shifted towards a higher frequency range when the perforation ratio of MPP increases. The results of the study proved that the MPP structure can help to enhance the sound absorption performance of oil palm fibre at a selected frequency range by choosing the right parameters like air cavity depth and perforation ratio.